Difficulties experienced by young people with Tourette syndrome in secondary school: a mixed methods description of self, parent and staff perspectives - Wadman, Ruth; Glazebrook, Cris; Beer, Charlotte Emma; Jackson, Georgina M. (BioMed Central, 2016)
Background: Tourette syndrome (TS) is a neurodevelopmental disorder characterised by motor and vocal tics. These involuntary movements and vocalizations can have a negative impact in the school environment. The paper presents a mixed methods description of the difficulties experienced by UK students with TS in secondary school, drawing on multiple perspectives.